Perdagangan Manusia (Human Trafficking) Transnasional Sebagai Ancaman Keamanan Maritim di Selat Malaka - Sartika Sartika; Agussalim Burhanuddin (LPPM Universitas Sains dan Teknologi Komputer, 2023)
Human trafficking is a crime that occurs not only in Indonesia. Nowadays, the modes of human trafficking are very varied and are still widespread. The Strait of Malacca, as an international trade route, is the busiest route which actually creates maritime threats such as human trafficking. Most cases of human trafficking involve women and children. The aim of this research is to determine human trafficking as a transnational organized crime that threatens maritime security and involves three coastal countries in the Malacca Strait, namely Malaysia, Singapore and Indonesia. The problem point is at the level of compliance with regulations. Due to the large scale of this crime, the UN or United Nations developed a protocol called Palermo which was later ratified and implemented by Indonesia in Law Number 21 of 2007 concerning the Crime of Human Trafficking. Apart from the regulatory aspect, the resolution of this problem is also through a cooperation forum between ASEAN countries, especially the three coastal countries in the Malacca Strait.